Fully-integrated delta-sigma analog-to-digital converters implemented in 90nm digital CMOS process for biomedical applications - Santelices, Lauren Angela Ollisa (2010)
The goal of this prject is to design, implement, and characterize fully-integrated delta-sigma analog-to-digital converters in 90nm digital CMOS process. Presented in this paper are four delta-sigma analog-to-digital converters using the following modulator topologies: (1) first-order, fully-differential continuous-time (2) first-order, fully-differential discrete-time (3) second-order, fully-differential continuous-time (4) second-order, fully-differential discrete-time. Converter specifications also presented include converter bandwidth, effective number of bits, oversampling ratio, and power consumption, which will be matched for suitability in biomedical instruments such as electromyogram (EMG). Delta-Sigma Analog-to-Digital Converters (Delta-Sigma ADC) exhibit higher resolution, ranging from 12 to 24 bits, compared to other ADC architectures. The common trade off for this feature, however, is slower speed, but the effect of this can be neglected if the chosen application is independent of sampling rate. Delta-sigma converters also boast of low market cost, lower power consumption, and higher signal-to-noise distortion ratio due to the concepts of oversampling, noise shaping, decimation, and digital filtering. The delta-sigma converter is composed of an analog and a digital block. The analog block, otherwise known as the modulator block, consists of an integrator, comparator, and a one-bit digital-to-analog converter and the digital block consists of a digital low pass filter and a decimator. Delta-Sigma ADC is most suitable for biomedical instrumentation because of the high resolution requirement. ADCs, in general, are commonly used for signal acquisition in biomedical technology. Delta-Sigma ADC also provides benefits such as small chip area, noise immunity outside ADC bandwidth, programmability for multiband applications, and reduced analog filtering. For this project, the Second-Order Discrete-Time Delta-Sigma ADC was found out to be suitable for implanted biomedical devices since it has the lowest power consumption among the four topologies with 64.5761µW. On the otherhand, First-Order Continuous-Time Delta-Sigma ADC has the smallest core area with 7,839 (μm)^2 and a relatively low power consumption at 106.3661µW. Thus, this topology is best suitable for mobile, battery-operated biomedical devices